Immunosuppression and Multiple Primary Malignancies in Kidney-Transplanted Patients: A Single-Institute Study. (22nd June 2015) - Santangelo, Michele L.; Criscitiello, Carmen; Renda, Andrea; Federico, Stefano; Curigliano, Giuseppe; Dodaro, Concetta; Scotti, Alessandro; Tammaro, Vincenzo; Calogero, Armando; Riccio, Eleonora; Pisani, Antonio; Carlomagno, Nicola
Abstract : Immunodeficiency is associated with higher cancer incidence. However, it is unknown whether there is a link between immunodeficiency and development of multiple primary malignancies. In the present study we analyse this link focusing on kidney-transplanted patients, as they are at higher risk of developing cancer due to the chronic assumption of immunosuppressants. We followed up 1200 patients who underwent kidney transplantation between 1980 and 2012. A total of 77/1200 kidney-transplanted patients developed cancer and 24 of them developed multiple cancers. Most multiple cancers were synchronous with a nonsignificant association between cancer and rejection episodes. In the general cancer population, one-ninth of patients are at higher risk of developing a second tumor over a lifetime; hence it would be reasonable to conclude that, from a merely theoretical and statistical viewpoint, long-term transplanted patients potentially have a higher risk of developing MPMs. However, data did not confirm this assumption, probably because these patients die before a second primary malignancy appears. Despite many observations on the increased incidence of different tumor types in immunodeficient patients and despite immunosuppression certainly being a predisposing factor for the multicancer syndrome, data so far are not robust enough to justify a correlation between immunodeficiency and multiple primary malignancies in transplanted patients.